Determinants of stock price volatility in Shariah-compliant firms - Aji Kumara Sukma; Nurofik Nurofik; Zulfikar Ali Ahmad (Universitas Sebelas Maret, 2023)
This study examines how inflation, exchange rates, interest rates, earnings per share, debt-to-equity ratio, and dividend payout ratio impact the volatility of stock prices among companies listed on the Indonesia Stock Exchange between 2015 and 2018. The research focuses on companies included in both the Indonesian Sharia Stock Index (ISSI) and the broader Indonesia Stock Exchange (BEI) during this period. This research obtained a total of 680 samples with a purposive sampling method. This paper also uses regression data panel models by Eviews 9 software. The results of the test show that interest rates and earnings per share positively affect stock price volatility. Meanwhile, inflation and debt-to-equity ratio negatively affect stock price volatility. Apart from that, the exchange rate and DPR do not affect stock price volatility. The findings in this article can contribute to the existing literature related to stock price volatility and also provide benefits to policies for company stakeholders.